The Influence of Online-Based Independent Learning Methods and Learning Motivation on Students' Entrepreneurship Skills UNP Kediri - Badrus, Badrus; Dwijayanto, Arik; Afif, Yusmicha Ulya (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
The study examines the effect of online-based independent study methods and learning motivation on students' entrepreneurship skills at the University of Nusantara PGRI (UNP) Kediri. This is important because several undergraduate graduates are suspected of being unemployed due to not having entrepreneurship skills to support their lives. The focus of this research includes 1) whether there is an effect of online-based independent study methods on student entrepreneurship skills, 2) whether there is any influence of learning motivation on student's entrepreneurship skills, and 3) whether there is an effect of online-based independent study methods and learning motivation on student entrepreneurship skills. This research uses descriptive quantitative data analysis using the ANOVA analysis technique. This analysis was used to examine the mean differences between groups. This will facilitate the analysis of several different sample groups with minimal risk of error. The population of this research is the students of the Faculty of Management and Economics, UNP Kediri. The sample consists of two classes in the Department of economics education. The results show 1) there is an influence of online-based independent study methods on students' entrepreneurship skills, 2) there is an influence of learning motivation on students' entrepreneurship skills, and 3) there is a mutual influence of online-based independent learning methods and learning motivation on student entrepreneurship skills.